The renin-angiotensin system plays a major role in voiding dysfunction of ovariectomized rats - Ramos-Filho, Antonio Celso S.; Faria, Juliana A.; Calmasini, Fabiano B.; Teixeira, Simone A.; Mónica, Fabíola Z.; Muscará, Marcelo N.; Gontijo, José A.R.; Anhê, Gabriel Forato; Zanesco, Angelina; Antunes, Edson (Elsevier, 2013)
Aims: The renin-angiotensin system (RAS) plays a major role in cardiovascular diseases in postmenopausal women, but little is known about its importance to lower urinary tract symptoms. In this study we have used the model of ovariectomized (OVX) estrogen-deficient rats to investigate the role of RAS in functional and molecular alterations in the urethra and bladder. Main methods: Responses to contractile and relaxant agents in isolated urethra and bladder, as well as cystometry were evaluated in 4-month OVX Sprague-Dawley rats. Angiotensin-converting enzyme activity and Western blotting for AT1/AT2 receptors were examined. Key findings: Cystometric evaluations in OVX rats showed increases in basal pressure, capacity and micturition frequency, as well as decreased voiding pressure. Angiotensin II and phenylephrine produced greater urethral contractions in OVX compared with Sham group. Carbachol-induced bladder contractions were significantly reduced in OVX group. Relaxations of urethra and bladder to sodium nitroprusside and BAY 41-2272 were unaffected by OVX. Angiotensin-converting enzyme activity was 2.6-fold greater (p < 0.05) in urethral tissue of OVX group, whereas enzyme activity in plasma and bladder remained unchanged. Expressions of AT1 and AT2 receptors in the urethra were markedly higher in OVX group. In bladder, AT1 receptors were not detected, whereas AT2 receptor expression was unchanged between groups. 17β-Estradiol replacement (0.1 mg/kg, weekly) or losartan (30 mg/kg/day) largely attenuated most of the alterations seen in OVX group. Significance: Prolonged estrogen deprivation leads to voiding dysfunction and urethral hypercontractility that are associated with increased ACE activity and up-regulation of angiotensin AT1/AT2 receptor in the urethral tissue. © 2013 Elsevier Inc. All rights reserved.
Keywords: Angiotensin receptors; Cystometry; Estrogen replacement therapy; Losartan; Urethra